St. Luke of Sikyon and his Byzantine Office From Cod. Sinaiticus gr. 568 - ANAGNOSTOU, Myrsini (Byzantina Symmeikta, 2025)
The aim of the present study is the publication of the hitherto unpublished liturgical office of Saint Luke of Sikyon. This office not only provides new information regarding his life, activities, and veneration—details not included in existing hagiographical sources—but also contributes to his identification with Saint Luke of Tauromenion, as has already been demonstrated in a previous study. The edition of the office is based on cod. Sinaiticus gr. 568.